1999
DOI: 10.1128/iai.67.5.2349-2356.1999
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon Production Is Critical for Protective Immunity to Infection with Blood-StagePlasmodium bergheiXAT but Neither NO Production nor NK Cell Activation Is Critical

Abstract: We have examined the roles of gamma interferon (IFN-γ), nitric oxide (NO), and natural killer (NK) cells in the host resistance to infection with the blood-stage malarial parasite Plasmodium berghei XAT, an irradiation-induced attenuated variant of the lethal strain P. berghei NK65. Although the infection withP. berghei XAT enhanced NK cell lytic activity of splenocytes, depletion of NK1.1+ cells caused by the treatment of mice with anti-NK1.1 antibody affected neither parasitemia nor IFN-γ production by their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Wild-type and TCR-d KO mice were infected with PbXAT. On days 14,16,18,20,22 and 24 post-infection (p.i. ), serum was taken from the PbXAT-infected WT mice.…”
Section: Passive Transfer Of Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type and TCR-d KO mice were infected with PbXAT. On days 14,16,18,20,22 and 24 post-infection (p.i. ), serum was taken from the PbXAT-infected WT mice.…”
Section: Passive Transfer Of Serummentioning
confidence: 99%
“…Inhibition of IFN-c signalling by gene knockout (KO) or injection of neutralizing anti-IFN-c antibody led to worsening of the parasitaemia, resulting in loss of fluctuation of the parasitaemia. 9,22 Interferon-c activates phagocytosis by macrophages and monocytes. Therefore, the fluctuations in the parasitaemia of bloodstage PbXAT parasites are strongly related to IFN-c.…”
Section: Introductionmentioning
confidence: 99%
“…The data presented confirm and extend published results for NO and other RNI (23), and show iNOS mRNA expression is altered during these murine malarias. These observations indicate that increased iNOS, particularly in the spleen, contributes to the control of malaria, although its presence may not be essential (36,37,46). However, RNI can cause adverse as well as beneficial effects and other experimental approaches, especially pharmacological studies, are required to determine the benefits and risks associated with changes in iNOS during malaria.…”
Section: Figurementioning
confidence: 99%
“…42,43 These susceptibility differences may again be explained by systemic compared with local transgene expression or the differential requirement of IFN-c for host survival. IFN-c production is required for survival of P. berghei and L. major infections, and IFN-c expression was decreased in SAP-IL-12 p40 transgenic mice, [42][43][44][45][46] whereas we have shown that mortality from a Sendai viral infection is independent of IFN-c production. 3 Lastly, overexpression of IL-12 p40 using the keratinocyte-specific (K14) promoter resulted in the spontaneous accumulation of immune cells (macrophages, lymphocytes, eosinophils, mast cells and neutrophils) in the skin and the development of an inflammatory skin disease.…”
Section: Discussionmentioning
confidence: 98%